Medical tube with high moisture permeability and preparation method thereof
By using porous silica aerogel powder, chitin fiber, PI fiber and other materials in medical pipes, combined with TPEE, PHA and other raw materials, a special moisture permeable structure is formed, which solves the problem of boiling existing medical pipes in high humidity environments. The problem of phenomenon has achieved the improvement of high moisture permeability and comprehensive performance.
Patent Information
- Application Number
- CN202411553566.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-02
- Publication Date
- 2025-02-14
AI Technical Summary
Existing medical pipes are prone to boiling in high humidity environments, which leads to the breeding of bacteria and viruses, increases the risk of medical infection, and also has the risk of liquid water penetration, and it is difficult to maintain flexibility and mechanical strength when improving moisture permeability.
Porous silica aerogel powder, chitin fiber, and PI fiber are used as moisture permeable fillers, combined with TPEE, PHA, epoxy ester plasticizer, and maleic anhydride grafts, through specific weight percentages and preparation methods, Form a special moisture permeability structure to improve the moisture permeability and comprehensive performance of the pipe.
It realizes excellent moisture permeability and waterproofness of medical pipes in high humidity environments, while maintaining better flexibility, antibacteriality and waterproofness, improving the safety of use.
Smart Images

Figure BDA0005115750030000051 
Figure BDA0005115750030000071 
Figure BDA0005115750030000091
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of medical devices, and more specifically, to a highly moisture-permeable medical tube and a preparation method thereof. Background Art
[0002] In the medical field, tubing is widely used, especially in implantable medical devices, where tubing needs to have good biocompatibility and mechanical properties. In order to meet these needs, researchers have developed a variety of materials and their combinations to improve the comprehensive performance of tubing. In recent years, with the development of new polymer materials, especially the application of biodegradable materials, medical tubing not only needs to have good flexibility and processing performance, but also needs to have excellent moisture permeability to adapt to a wider range of clinical applications.
[0003] In response to these requirements, existing medical tubing is usually made of polymer materials, such as polyurethane, polyethylene, silicone rubber, etc., in order to improve its mechanical properties and biocompatibility through compounding or blending between materials. In addition, in order to make the tubing have better air permeability and moisture permeability, porous and highly absorbent fillers are usually added to improve moisture permeability, but this also leads to reduced waterproofness.
[0004] In particular, medical tubing used in ventilator circuits and infusion tubes is still prone to boiling in high humidity environments, leading to the growth of bacteria and viruses, increasing the risk of medical infection, and there is also the risk of liquid water penetration.
[0005] However, in the existing medical tubing manufacturing technology, although some properties of the material can be improved by the above means, while improving the moisture permeability of the material, the flexibility and mechanical strength of the tubing are often affected, making it difficult to meet the comprehensive performance requirements required in existing clinical applications. Therefore, how to improve the moisture permeability of medical tubing while maintaining good flexibility has become a key issue that needs to be solved urgently. Summary of the invention
[0006] In order to improve the moisture permeability and obtain better antibacterial properties, flexibility and waterproofness, the present application provides a high moisture permeability medical tube and a preparation method thereof.
[0007] In a first aspect, the present application provides a highly moisture-permeable medical tube, comprising a tube body, wherein the tube body is composed of the following raw materials in the following weight percentages: TPEE54-70% PHA10-20% Epoxy ester plasticizer 3-8% Maleic anhydride grafted 1-5% 12-18 parts of moisture permeable filler The balance is antioxidant; The moisture permeable filler is composed of porous silica aerogel powder, chitin fiber and PI fiber in a weight ratio of (2-5):(1-3):1.
[0008] The weight ratio range in the above scheme is the best choice for this application, wherein the content of TPEE is 54-70%, which, in combination with other raw materials, can make the medical tubing have better flexibility; the amount of PHA is 10-20%, which interacts with the moisture permeable filler to effectively improve the air permeability, moisture permeability and antibacterial properties of the tubing; and the proportion of epoxy ester plasticizer is 3-8%, which further improves the flexibility and processing performance of the tubing, promotes the cross-linking of the raw material system and improves the waterproofness, and also promotes the dispersion of the moisture permeable filler; The content of maleic anhydride graft is 1-5%, which acts as a compatibilizer to improve the compatibility between the moisture permeable filler and PHA and TPEE; the moisture permeable filler is composed of porous silica aerogel powder, chitin fiber, and PI fiber, and the dosage is 12-18%, which can cooperate with TPEE, PHA, epoxy ester plasticizer, and maleic anhydride graft to form a special moisture permeable structure, which can significantly improve the moisture permeability of the pipe, and make the medical pipe have better flexibility, antibacterial and waterproof properties, thereby improving the safety of the medical pipe.
[0009] In summary, porous silica aerogel powder, chitin fiber, and PI fiber, as moisture-permeable fillers, can form a special moisture-permeable structure in the raw material system of medical tubing, which has a better barrier effect on large-volume liquids and better permeability to gaseous and small-volume water. Therefore, the medical tubing has both good moisture permeability and waterproofness. Then, it interacts with TPEE, PHA, epoxy ester plasticizers, and maleic anhydride grafts, so that the obtained medical tubing has higher moisture permeability, and at the same time has better flexibility, antibacterial properties, and waterproofness.
[0010] Preferably, the porous silica aerogel powder, chitin fiber and PI fiber are composed in a weight ratio of 2.3:1.8:1.
[0011] By adopting the above technical solutions, porous silica aerogel powder has the characteristics of low density and high porosity, which can significantly reduce the weight of medical tubing and provide moisture permeability and reinforcement; chitin fiber has good biocompatibility, antibacterial properties and hygroscopicity, which can improve the safety, antibacterial effect and moisture permeability of medical tubing; PI fiber has the characteristics of high strength and high temperature resistance, which enhances the mechanical properties and durability of medical tubing. The three are used in combination at a weight ratio of 2.3:1.8:1, and the combined effect significantly improves the moisture permeability and comprehensive performance of medical tubing.
[0012] Preferably, the mesh size of the porous silica aerogel powder is 800-1000 mesh.
[0013] By adopting the mesh size and density of the above porous silica aerogel powder, it is possible to form a moisture-permeable and liquid water-proof structure in the medical tubing system in combination with chitin fiber and PI fiber, so that the medical tubing has good moisture permeability.
[0014] Preferably, the chitosan fiber has a diameter of 20-50 microns and a length of 100-200 microns; the PI fiber has a diameter of 10-20 microns and a length of 50-120 microns.
[0015] The particle size of chitin fiber is 20-50 microns and the length is 100-200 microns. The particle size of PI fiber is 10-20 microns and the length is 50-120 microns. This structure, combined with porous silica aerogel powder, can form a special pore structure, significantly improve the moisture permeability of the material, and prevent liquid water. At the same time, combined with other raw materials, the overall performance of the pipe is better.
[0016] Preferably, the porous silica aerogel powder has a specific surface area of 700-800 m2 / g, a pore size of 50-100 nm, and a porosity of 80-90%.
[0017] The porous silica aerogel powder has a specific surface area of 700-800 square meters / gram, a pore size of 50-100nm, and a porosity of 80-90%, so that the moisture permeable filler has a more excellent pore structure, thereby effectively improving the moisture permeability and mechanical strength of the medical tube.
[0018] Preferably, the epoxy ester plasticizer is one or more of epoxy acetylated ricinoleic acid methyl ester, epoxy soybean oil acrylate, and epoxy soybean oil octyl ester.
[0019] Epoxy soybean oil acrylate, epoxy acetylated ricinoleic acid methyl ester, etc., because of the epoxy groups in their molecular structure, can react chemically or physically with the polymer matrix, thereby enhancing the crosslinking density and mechanical strength between the polymer molecular chains. This helps to improve the waterproof performance of the material. At the same time, it has a lower surface tension, making it more difficult for water droplets to spread and penetrate on the surface of the material, thereby improving the hydrophobicity of the material, and in combination with the moisture-permeable filler of this application, it can achieve better waterproof and moisture-permeability. It makes it easy for large-volume water or water droplets to be blocked during the penetration process, and atomized water can pass through easily. Further, Preferably, the maleic anhydride grafted product is acrylate maleic anhydride grafted product and / or maleic anhydride grafted POE.
[0020] Among them, the acrylate maleic anhydride grafted product is preferably American Trinseo EA101 and the maleic anhydride grafted POE is preferably Mitsui MH5020.
[0021] The use of acrylate maleic anhydride grafted products and / or maleic anhydride grafted POE can provide better compatibility and promote the combination of the raw material system, thereby further improving the overall performance.
[0022] Preferably, the moisture permeable filler is a modified moisture permeable filler, and the modified moisture permeable filler is made of the following raw materials in percentage by weight: γ-Piperazinylpropylmethyldimethoxysilane 0.7-1.3% Aminopropyl dicapped polydimethylsiloxane 0.1-0.8% Alkoxylated polyol 0.3-1% Ammonium persulfate 0.01-0.03% Moisture permeable filler 35-50% The balance is diluent.
[0023] The use of modified breathable fillers forms a coating on the surface of the breathable fillers. γ-piperazinepropylmethyldimethoxysilane is used as a coupling agent to form a film on the surface of the filler, and interacts with aminosilane and alkoxylated polyols under the action of ammonium persulfate, which improves the dispersibility of the filler and its compatibility with the polymer matrix. Aminopropyl dicapped polydimethylsiloxane and alkoxylated polyols work together to form a stable coating film. The film-forming agent promotes the reaction and film-forming process, further improving the uniform dispersion of the filler and the overall moisture permeability of the material. When compounded with TPEE, PHA, epoxy ester plasticizers, and maleic anhydride grafts, the moisture permeability of medical tubing can be further improved, and it can also have better flexibility, antibacterial properties, and waterproof properties.
[0024] Preferably, the modified moisture permeable filler is prepared by the following method: According to weight percentage, γ-piperazinepropylmethyldimethoxysilane, alkoxylated polyol, aminopropyl dicapped polydimethylsiloxane, moisture permeable filler, diluent, alkoxylated polyol and ammonium persulfate are weighed and mixed evenly, heated to 65-75° C., stirred for 10-30 minutes, distilled under reduced pressure and dried to obtain a modified moisture permeable filler.
[0025] By adopting the above technical solution, the dispersion and compatibility of the moisture permeable filler are improved, thereby further improving the moisture permeability and mechanical strength of the medical tubing. Specifically, the modified moisture permeable filler is prepared by a specific method, so that a stable coating film is formed on the surface of the filler, the dispersion state of the filler in the raw material system is improved, and the interface bonding force between the filler and the polymer matrix is enhanced, so that the medical tubing has better comprehensive performance.
[0026] In a second aspect, a method for preparing a highly moisture permeable medical tube is prepared by the following method: According to the weight percentage, TPEE, PHA, epoxy ester plasticizer, maleic anhydride graft, moisture permeable filler and antioxidant are weighed and mixed evenly, heated to melt, and then extruded to obtain medical tubing.
[0027] By adopting the above technical solution, the high moisture permeability medical tubing is mixed with a specific weight percentage of TPEE, PHA, plasticizer, maleic anhydride graft, moisture permeable filler and antioxidant during the preparation process, thereby improving the flexibility and moisture permeability of the tubing, while ensuring the compatibility and processing performance between the materials. The final extruded medical tubing has excellent moisture permeability and good flexibility, as well as antibacterial and waterproof properties.
[0028] In summary, this application has the following beneficial effects: 1. By using porous silica aerogel powder, chitin fiber, and PI fiber as moisture-permeable fillers, a special moisture-permeable structure can be formed in the raw material system of medical tubing, which has a better barrier effect on large-volume liquids and better permeability to gaseous and small-volume water. Therefore, the medical tubing has both good moisture permeability and waterproofness. Then, it interacts with TPEE, PHA, epoxy ester plasticizers, and maleic anhydride grafts, so that the obtained medical tubing has higher moisture permeability, and at the same time has better flexibility, antibacterial properties, and waterproofness.
[0029] 2. γ-piperazinepropylmethyldimethoxysilane, aminopropyl dicapped polydimethylsiloxane and alkoxylated polyol interact with each other to improve the dispersibility of the moisture permeable filler, and under the action of ammonium persulfate, a coating film with good compatibility is formed on the surface of the moisture permeable filler, thereby improving its compatibility with the pipe raw material system, further improving and combining better flexibility, antibacterial properties, moisture permeability, and waterproof properties. DETAILED DESCRIPTION
[0030] The present application is further described in detail below with reference to the embodiments.
[0031] PTEE, TPEE Keyflex BT7069G from LG Chemical of South Korea; The number average molecular weight of PHA is 30,000-50,000; The average molecular weight of aminopropyl dicapped polydimethylsiloxane is 1000-2000; The antioxidant is antioxidant 1010; Epoxidized soybean oil acrylate CAS No. 91722-14-4; The molecular structure of epoxidized soybean octyl ester is as follows: Alkoxylated polyol, brand model Pasto polyol 3610, contains three primary hydroxyl groups and its hydroxyl value is 610±25mgKOH / g.
[0032] Preparation example of modified moisture permeable filler Preparation Example 1 A modified moisture permeable filler is prepared by the following method: According to weight percentage, 0.7% γ-piperazinepropylmethyldimethoxysilane, 0.8% aminopropyl dicapped polydimethylsiloxane, 35% moisture permeable filler, 63.19% diluent, 0.3% alkoxylated polyol, and 0.01% ammonium persulfate were weighed and mixed evenly, heated to 65°C, stirred for 10 minutes at a speed of 100 r / min, heated to 100°C, and subjected to reduced pressure distillation at -0.01 MPa to completely evaporate the diluent. The obtained solid was placed in an oven at 50°C and baked for 2 hours to obtain a modified moisture permeable filler.
[0033] The diluent is a 50% ethanol solution by mass. The moisture permeable filler is composed of porous silica aerogel powder, chitin fiber, and PI fiber in a weight ratio of 2.3:1.8:1. The mesh number of the porous silica aerogel powder is 800 mesh. The specific surface area of the porous silica aerogel powder is 700 square meters / gram, the pore size is 50nm, and the porosity is 90%. The average line diameter of the chitin fiber is 20 microns and the length is 100 microns; the average line diameter of the PI fiber is 10 microns and the length is 50 microns.
[0034] Preparation Example 2 The difference between Preparation Example 2 and Preparation Example 1 is that the modified moisture permeable filler is prepared by the following method: According to weight percentage, 1% γ-piperazinepropylmethyldimethoxysilane, 0.5% aminopropyl dicapped polydimethylsiloxane, 40% moisture permeable filler, 57.98% diluent, 0.5% alkoxylated polyol, and 0.02% ammonium persulfate were weighed and mixed evenly, heated to 70°C, stirred at a speed of 100 r / min for 20 minutes, heated to 100°C, and vacuum distilled at -0.01 MPa to completely evaporate the diluent. The obtained solid was placed in an oven at 50°C and baked for 2 hours to obtain a modified moisture permeable filler (the rest is the same as Preparation Example 1).
[0035] Preparation Example 3 The difference between Preparation Example 2 and Preparation Example 1 is that the modified moisture permeable filler is prepared by the following method: According to the weight percentage, 1.3% γ-piperazinepropylmethyldimethoxysilane, 0.1% aminopropyl dicapped polydimethylsiloxane, 50% moisture permeable filler, 47.57% diluent, 1% alkoxylated polyol, and 0.03% ammonium persulfate were weighed and mixed evenly, heated to 75°C, stirred for 30 minutes at a speed of 100 r / min, heated to 100°C, and vacuum distilled at -0.01 MPa to completely evaporate the diluent. The obtained solid was placed in an oven at 50°C and baked for 2 hours to obtain a modified moisture permeable filler (the rest is the same as Preparation Example 1).
[0036] Preparation Comparative Example Preparation Comparative Example 1 The difference between Preparation Comparative Example 1 and Preparation Example 1 is that the aminopropyl di-terminated polydimethylsiloxane is replaced by an equal amount of γ-piperazinepropylmethyldimethoxysilane.
[0037] Preparation Comparative Example 2 The difference between Preparation Comparative Example 2 and Preparation Example 1 is that an equal amount of the alkoxylated polyol is replaced by γ-piperazinylpropylmethyldimethoxysilane. Example
[0038] Example 1 According to the weight percentage, 54% TPEE, 20% PHA, 8% epoxy ester plasticizer, 5% maleic anhydride graft, 12% moisture permeable filler and 1% antioxidant were weighed and put into a high-speed mixer, and mixed at 300 r / min for 5 minutes. The obtained materials were put into a twin-screw extruder at a temperature of 200°C for melt mixing and extrusion, and then granulated by water cooling. The obtained pellets were put into a pipe extruder at a temperature of 205°C for extrusion molding to obtain medical pipes.
[0039] The moisture permeable filler is composed of porous silica aerogel powder, chitin fiber and PI fiber in a weight ratio of 2:1:1.
[0040] The mesh number of the porous silica aerogel powder is 800 meshes, the specific surface area of the porous silica aerogel powder is 700 square meters / gram, the pore diameter is 50 nm, and the porosity is 90%.
[0041] The average diameter of chitin fiber is 20 microns and the length is 100 microns; the average diameter of PI fiber is 10 microns and the length is 50 microns.
[0042] The epoxy ester plasticizer is methyl epoxy acetylic acid ricinoleate.
[0043] The maleic anhydride grafted product is an acrylate maleic anhydride grafted product.
[0044] Example 2-3 The difference between Example 2-3 and Example 1 is that the amount and composition of the raw materials are different, as shown in Table 1; Table 1 Amount (%) and composition of raw materials in Examples 1-3 Example 4 The difference between Example 4 and Example 2 is that the moisture permeable filler is composed of porous silica aerogel powder, chitin fiber and PI fiber in a weight ratio of 5:3:1.
[0045] Example 5 The difference between Example 5 and Example 2 is that the moisture permeable filler is composed of porous silica aerogel powder, chitin fiber and PI fiber in a weight ratio of 2.3:1.8:1.
[0046] Example 6 The difference between Example 6 and Example 5 is that the mesh number of the porous silica aerogel powder is 1000 mesh. The specific surface area of the porous silica aerogel powder is 800 square meters / gram, the pore size is 100nm, and the porosity is 80%. The average diameter of the chitin fiber is 50 microns and the length is 200 microns; the average diameter of the PI fiber is 20 microns and the length is 120 microns.
[0047] Example 7 The difference between Example 7 and Example 5 is that the epoxy ester plasticizer is composed of epoxy acetylated ricinoleic acid methyl ester and epoxy soybean oil acrylate in a weight ratio of 1:1.
[0048] Example 8 The difference between Example 8 and Example 7 is that the moisture permeable filler is the modified moisture permeable filler obtained in Preparation Example 1.
[0049] Examples 9-12 The difference between Examples 9-12 and Example 8 is that the sources of the modified moisture permeable filler are different, as shown in Table 2; Table 2 Sources of modified moisture permeable fillers of Examples 8-12 Example Source of modified moisture permeable filler Example 8 Preparation Example 1 Example 9 Preparation Example 2 Example 10 Preparation Example 3 Embodiment 11 Preparation Comparative Example 1 Example 12 Preparation Comparative Example 2 Comparative Example Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that the moisture permeable filler is replaced by diatomaceous earth.
[0050] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that the moisture permeable filler is porous silica aerogel powder.
[0051] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that the moisture permeable filler is chitin fiber.
[0052] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that the moisture permeable filler is PI fiber Comparative Example 5 The difference between Comparative Example 5 and Example 1 is that the moisture permeable filler is composed of porous silica aerogel powder and chitin fiber in a weight ratio of 2:1.
[0053] Comparative Example 6 The difference between Comparative Example 6 and Example 1 is that the epoxy ester plasticizer is replaced by trioctyl citrate.
[0054] Comparative Example 7 The difference between Comparative Example 7 and Example 1 is that PHA is replaced by TPEE in equal amounts.
[0055] Performance testing Detection method / test method Water vapor permeability: The pellets obtained in Examples 1-12 and Comparative Examples 1-7 were extruded at a temperature of 205°C and then calendered into a 0.1 mm thick test film. Referring to GB / T 1037-1988 standard, a W3 / 031 water vapor transmission rate tester was used.
[0056] Mechanical properties: The pellets obtained in Examples 1-12 and Comparative Examples 1-7 were placed in an injection molding machine for injection molding into test samples at an injection molding temperature of 208° C. The tensile strength and elongation at break were tested with reference to ASTM412.
[0057] Water permeability: 24-hour water permeability test: The medical tubing obtained in Examples 1-12 and Comparative Examples 1-7 was cut into 20 cm pieces, placed in an oven at 50°C for drying for 30 min, weighed and recorded as g1, and then completely immersed in water at 23°C and allowed to stand for 24 h. The tube was taken out, the surface moisture was blown dry with a hair dryer, and then weighed and recorded as g2. The mass change rate was calculated.
[0058] Antibacterial property: The test samples were tested according to the national standard GB / T 31402-2015 "Test method for antibacterial performance of plastic surfaces", and the antibacterial properties of Escherichia coli and Staphylococcus aureus were tested respectively, and the average value was taken and the antibacterial rate was recorded; Table 3 Experimental data of Examples 1-12 and Comparative Examples 1-7 Combining Example 1 and Comparative Examples 1-5 and Table 3, it can be seen that the moisture permeability, elongation at break, and tensile strength of Comparative Examples 1-5 are greater than those of Comparative Example 1, the mass growth rate of Comparative Examples 1-5 is greater than the mass growth rate of Example 1, and the antibacterial rates of Comparative Examples 1, 2, and 4 are lower than that of Example 1, indicating that the present application forms a special structure in the medical tubing system by compounding porous silica aerogel powder, chitin fiber, and PI fiber, which can play a better waterproof and moisture permeability role, and can also play a better antibacterial and mechanical properties.
[0059] By comparing Example 7 and Example 8 and combining with Table 3, it can be seen that the mass growth rate of Example 8 is reduced to 5.6%, and the moisture permeability, antibacterial rate, elongation at break, and tensile strength of Example 8 are all improved, indicating that the modified moisture permeable filler prepared by the present application can be compatible with the medical tubing raw material system and form a stable and uniform special structure, which is beneficial to moisture permeability while preventing a large volume of water from passing through, thereby obtaining better comprehensive performance.
[0060] By comparing Example 8 with Examples 11-12 and combining with Table 3, it can be seen that the moisture permeability, elongation at break, and tensile strength of Examples 13-14 are all less than those of Example 8, while the mass growth rate is greater than that of Example 8, indicating that the modified moisture permeable filler prepared by the present application through the interaction of 0.7-1.3% of γ-piperazinylpropylmethyldimethoxysilane, 0.1-0.8% of aminopropyl dicapped polydimethylsiloxane, 0.3-1% of alkoxylated polyol, 0.01-0.03% of ammonium persulfate, 35-50% of moisture permeable filler, and the balance of diluent is tightly integrated with the raw material system of the medical tubing, and interacts with TPEE, PHA, epoxy ester plasticizers, and maleic anhydride grafts, so that the medical tubing has better waterproofness, moisture permeability, antibacterial properties and mechanical properties.
[0061] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A highly moisture-permeable medical tube, comprising a tube body, characterized in that: The tube body is composed of the following raw materials in weight percentage: TPEE54-70% PHA10-20% Epoxy ester plasticizer 3-8% Maleic anhydride grafted 1-5% 12-18 parts of moisture permeable filler The balance is antioxidant; The moisture permeable filler is composed of porous silica aerogel powder, chitin fiber and PI fiber in a weight ratio of (2-5): (1-3):
1.
2. The highly moisture-permeable medical tubing according to claim 1, characterized in that: The porous silica aerogel powder, chitin fiber and PI fiber are composed in a weight ratio of 2.3:1.8:
1.
3. The highly moisture-permeable medical tubing according to claim 1, characterized in that: The mesh size of the porous silica aerogel powder is 800-1000 meshes.
4. The highly moisture permeable medical tube according to claim 1, characterized in that: The chitosan fiber has a diameter of 20-50 microns and a length of 100-200 microns; the PI fiber has a diameter of 10-20 microns and a length of 50-120 microns.
5. The highly moisture-permeable medical tubing according to claim 1, characterized in that: The porous silica aerogel powder has a specific surface area of 700-800 square meters / gram, a pore diameter of 50-100 nm, and a porosity of 80-90%.
6. The highly moisture-permeable medical tubing according to claim 1, characterized in that: The epoxy ester plasticizer is one or more of epoxy acetylated ricinoleic acid methyl ester, epoxy soybean oil acrylate, and epoxy soybean oil octyl ester.
7. The highly moisture-permeable medical tube according to claim 1, characterized in that: The maleic anhydride grafted product is acrylate maleic anhydride grafted product and / or maleic anhydride grafted POE.
8. A highly moisture permeable medical tube according to any one of claims 1 to 7, characterized in that: The moisture permeable filler is a modified moisture permeable filler, and the modified moisture permeable filler is made of the following raw materials in percentage by weight: γ-Piperazinepropylmethyldimethoxysilane 0.7-1.3% Aminopropyl dicapped polydimethylsiloxane 0.1-0.8% Alkoxylated polyol 0.3-1% Ammonium persulfate 0.01-0.03% Moisture permeable filler 35-50% The balance is diluent.
9. The highly moisture-permeable medical tubing according to claim 8, characterized in that: The modified moisture permeable filler is prepared by the following method: According to weight percentage, γ-piperazinepropylmethyldimethoxysilane, alkoxylated polyol, aminopropyl dicapped polydimethylsiloxane, moisture permeable filler, diluent, alkoxylated polyol and ammonium persulfate are weighed and mixed evenly, heated to 65-75° C., stirred for 10-30 minutes, distilled under reduced pressure and dried to obtain a modified moisture permeable filler.
10. A method for preparing a highly moisture-permeable medical tube according to any one of claims 1 to 9, characterized in that: Prepared by the following method: According to the weight percentage, TPEE, PHA, epoxy ester plasticizer, maleic anhydride graft, moisture permeable filler and antioxidant are weighed and mixed evenly, heated to melt, and then extruded to obtain medical tubing.